Gait parameters in patients with diabetes mellitus - Cristina Elena Prado Teles Fregonesi; Marcela Regina Camargo (Universidade Federal de Santa Catarina, 2010)
Diabetes mellitus is a chronic disease that results in sensorimotor alterations. These changes affect balance and walking and predispose affected patients to falls. The aim of this review was to identify studies in the recent literature that assess gait parameters and aspects involved in walking. The MEDLINE, SciELO, LILACS and PEDro databases were searched using the following combination of keywords: diabetic neuropathies x gait; diabetes mellitus x gait, and diabetic foot x gait. After the application of selection criteria, 15 articles were retrieved, summarized, discussed, and are included in this review. Diabetic neuropathy was found to lead to deficits in step amplitude, gait velocity and gait cadence on flat surfaces, without sudden changes in direction or stops, and to balance and coordination deficits on inclined and uneven terrain. Diabetic neuropathies also increase plantar pressure rates and lead to difficulties in the terminal stance phase and pre-swing phase due to changes in triceps surae activation. Thus, the next initial contact occurs in an inadequate manner, with the forefoot and without absorption of shocks.